Synthesis and Antioxidant Activity of Some 2-Amino-4-aryl-3-cyano-7-(dimethylamino)-4H-chromenes - FOROUMADI, ALIREZA; DEHGHAN, GHOLAMREZA; SAMZADEH-KERMANI, ALIREZA; ARABSORKHI, FATEMEH; SORKHI, MAEDEH; SHAFIEE, ABBAS; ABDOLLAHI, MOHAMMAD (Asian Journal of Chemistry, 2010)
A new series of 2-amino-4-aryl-3-cyano-7-(dimethylamino)-4H-chromenes was synthesized by the condensation of 3-(dimethylamino)phenol, an aromatic aldehyde and malonitrile in ethanol containing piperidine. The assignments of the structure of all the newly synthesized compounds were based on elemental analysis and spectral data (IR, Mass, 1H NMR). The antioxidant activity of the synthesized compounds was determined by Ferric Reducing Antioxidant Power (FRAP) and DPPH free radical scavenging methods. Several compounds showed significant antioxidant activity.